Parental Empathy, Aggressive Parenting, and Child Adjustment in a Noncustodial High-Risk Sample - Bi, Shuang (Journal of interpersonal violence, 2021)
This study examined the relations between parental empathy, parenting physical aggression, parental psychological control, and child adjustment in a sample of parents who had their children removed from their custody because of child abuse or neglect. Twenty parents between 24 and 40 years of age (M = 31.15, SD = 4.85; 85% female) with a child aged between 1.5 and 16 years (M = 6.5, SD = 3.88; 70% boys) participated in the study. Our sample was comprised of relatively racially diverse and low-income parents, with 40% from racial minority groups and 70% below the poverty line. Parents were recruited from a local nonprofit organization providing court-mandated parenting classes. Parents reported on their dispositional empathy, physical aggression toward children, psychological control and child internalizing and externalizing symptoms in an interview format. Parents also reported on empathy for their children through a semistructured interview; their empathy was later coded by trained research assistants. Bivariate correlation analyses revealed that parental empathy in the parent–child relationship negatively correlated with parental psychological control. Greater parental psychological control significantly correlated with greater approval of corporal punishment. Moreover, in the subsample of older children (6 years old and above), greater parental dispositional empathy was associated with greater child externalizing symptoms. Further exploratory analyses showed that associations between parental empathy, psychological control, and spanking attitudes differed across parents of boys and of girls. This study highlights the importance of examining empathy specific to the parent–child relationship in addition to dispositional empathy to predict parenting aggression. More importantly, studies should focus on a more covert form of parenting aggression, parental psychological control, in addition to physical aggression.